(untitled) (Journal of the Management Sciences, 2024)
This study examined the effect of e-commerce utilization on the operational efficiency of small and medium-sized enterprises (SMEs) in Anambra State, Nigeria, by deploying the Vector Autoregression (VAR) model. The analysis focused on the impact of online sales, digital marketing, e-payment systems, website quality, and social media engagement on operational efficiency. Data were collected from a representative sample of SMEs across Anambra State and analysed using econometric regression techniques. The empirical results indicated that online sales (β = 0.28, p < 0.01) and digital marketing (β = 0.33, p < 0.01) have a statistically significant positive impact on operational efficiency, highlighting their critical role in enhancing SME performance. E-payment systems also exhibited a positive effect (β = 0.21, p < 0.05), emphasizing the importance of efficient transaction processes. Website quality was positively correlated with operational efficiency (β = 0.25, p < 0.05), suggesting that a user-friendly online presence is essential for operational success. However, social media engagement showed a complex relationship (β = 0.12, p > 0.05), indicating that while beneficial for brand awareness, its direct impact on operational efficiency may be mediated by other factors. The VAR model also revealed significant dynamic interactions among the variables, with Granger causality tests confirming that changes in online sales and digital marketing significantly predict future changes in operational efficiency. Impulse response functions further demonstrated that shocks to online sales and digital marketing have lasting positive effects on operational efficiency over time. These findings provided valuable insights for SME owners, policymakers, and stakeholders in Anambra State. They underscored the necessity for continuous investment in e-commerce infrastructure and strategic utilization of online sales and digital marketing to sustain and enhance operational efficiency. The study concluded that targeted ecommerce practices were instrumental in driving SME performance in the digital economy